Positive liquidity spillovers from sovereign bond-backed securities - Peter G. Dunne (European Systemic Risk Board (ESRB), European System of Financial Supervision, 2018)
There are competing arguments about the likely effects of Sovereign Bond-Backed Securitisation on the liquidity of sovereign bond markets. By analysing hedging and diversification opportunities, this paper shows that positive liquidity spillovers would dominate or at least constrain the extent of any negative effects. This relies on dealers using Sovereign Bond-Backed Securities as instruments to hedge inventory risk and it assumes that they diversify their activities widely across euro area sovereign markets. Through a simple arbitrage relation, the existence of low-cost hedging and diversification opportunities limits the divergence of bid-ask spreads between national and SBBS markets. This is demonstrated using estimated SBBS yields ( à la Schönbucher (2003)).
Keywords: E44; G12; G24; C22; C53; C58; C63; 330; Safe Assets; Securitsation; Dealer Behaviour; Liquidity Bid-Ask Spread